A new species of Burkholderia isolated from sugarcane roots promotes plant growth. Issue 2 (19th December 2013) - Paungfoo‐Lonhienne, Chanyarat; Lonhienne, Thierry G. A.; Yeoh, Yun Kit; Webb, Richard I.; Lakshmanan, Prakash; Chan, Cheong Xin; Lim, Phaik‐Eem; Ragan, Mark A.; Schmidt, Susanne; Hugenholtz, Philip
Summary Sugarcane is a globally important food, biofuel and biomaterials crop. High nitrogen (N) fertilizer rates aimed at increasing yield often result in environmental damage because of excess and inefficient application. Inoculation with diazotrophic bacteria is an attractive option for reducing N fertilizer needs. However, the efficacy of bacterial inoculants is variable, and their effective formulation remains a knowledge frontier. Here, we take a new approach to investigating diazotrophic bacteria associated with roots using culture‐independent microbial community profiling of a commercial sugarcane variety (Q208A) in a field setting. We first identified bacteria that were markedly enriched in the rhizosphere to guide isolation and then tested putative diazotrophs for the ability to colonize axenic sugarcane plantlets (Q208A) and promote growth in suboptimal N supply. One isolate readily colonized roots, fixed N2 and stimulated growth of plantlets, and was classified as a new species, Burkholderia australis sp. nov. Draft genome sequencing of the isolate confirmed the presence of nitrogen fixation. We propose that culture‐independent identification and isolation of bacteria that are enriched in rhizosphere and roots, followed by systematic testing and confirming their growth‐promoting capacity, is a necessary step towards designing effective microbial inoculants.